N conjugative transfer system of plasmid pCU1. - Thatte, V (1985)
The mating and plasmid DNA transfer functions in Escherichia coli K-12 strains that are determined by the IncN group plasmid pCU1 are specified by a single 19.4-kilobase (kb) segment of the 39-kb plasmid. Analysis of this tra region by transposon Tn5 mutagenesis and by complementation tests indicated that a subset of tra comprising six complementation groups (presumably transcription units) determines sensitivity to the N pilus-specific bacteriophages IKe and PRD1. Deletion derivatives and molecular clones that contained only this part of tra conferred sensitivity to IKe and PRD1 and the ability to produce N pili without conferring the Tra phenotype. The entire tra region contained two other complementation groups. If the 19.4-kb tra region is interrupted by DNA that is irrelevant to the Tra phenotype, such DNA must be less than 2 kb long. There are two regions within tra where this is a possibility. These observations are compared with those obtained recently with a related plasmid.